Problematika Fonologi Pada Pembelajaran Bahasa Arab Kelas IX Madrasah Tsanawiyah (Studi Kasus Terhadap Buku Ajar) - Wahyu Dwi Taryanto (Mahira: Journal of Arabic Studies & Teaching, 2023)
Language learning, especially Arabic in Indonesia, often faces various kinds of linguistic problems, one of which is the phonological problems that exist in learning Arabic. Phonology is an element of language that discusses various types of sounds to the places where they come out. Of course, this element is important and very highly recommended to be discussed by students, outside of the four Arabic language proficiency or more commonly known as maharatul lughawiyah. Phonology problems are not necessarily born due to the mistakes of speakers alone, but also from teaching materials such as books used for teaching and learning, if there are errors in writing in the book, it will have an impact on pronunciation errors or phonology problems, which will also have an impact on misinterpretation in the sentences in the book. Therefore, this study discusses various kinds of errors that exist in the Class IX Arabic book Madrasah Tsanawiyah printed kami Madrasah, which is expected to be used as reference material for printing books in later prints, to the lack of errors in writing Arabic in the book.